Communicative adaptation as a factor in the social rehabilitation of people with visual impairment - Чорна, Валентина; Гуменюк, Наталія; Ангельська, Вікторія; Ордатій, Наталія; Кривецька, Неля; Шемет, Вікторія (Psychosomatic Medicine and General Practice, 2025)
According to unofficial data as of 2020, there were 144 thousand citizens with visual impairments in Ukraine, among whom approximately 40 thousand people had significant visual impairment, which led to profound disability of these people. The number of visually impaired people is about 1 thousand people per million population. Of this number, more than 10 thousand children have the status of disabled people due to diseases of the organ of vision. Every year, about 12 thousand people are recognized as disabled in Ukraine due to visual impairments. At the same time, modern society is increasingly oriented towards the principles of inclusion and equal opportunities, which necessitates a rethinking of approaches to the social rehabilitation of persons with disabilities, in particular people with visual impairments. Effective communication is one of the key factors in the successful integration of such persons into the social environment, since it is through communication that a sense of belonging, self-esteem, and social competence is formed. Communicative adaptation helps blind people overcome barriers to perception, develop interaction and self-expression skills, which contributes to their self-realization and active participation in community life. Interpersonal communication remains an important component in the adaptation of people with visual impairments. For people with visual impairments, the communication process has specific features due to sensory limitations, psychological barriers and social conditions. Loss or significant reduction in visual perception changes the structure of communicative interaction, since a significant part of non-verbal information becomes inaccessible. This creates additional difficulties in establishing contacts, understanding the emotional state of the interlocutor and maintaining social ties. In this context, public associations play an important role, among which the Ukrainian Society of the Blind (UTOS) remains one of the key centers of assistance and support for the blind.